1993
DOI: 10.1111/j.1432-1033.1993.tb18065.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of fatty‐acid‐binding protein in bovine heart are coded by distinct mRNA

Abstract: In the course of our studies on structure/function relationships of fatty‐acid‐binding proteins, we reported earlier that the two isoforms of the 15‐kDa cardiac fatty‐acid‐binding protein (cFABP) from bovine heart only differ in one position; Asn98 in pl 5.1‐cFABP; Asp98 in pI 4.9‐cFABP [Unterberg, C., Börchers, T., Højrup, P., Knudsen, J. and Spener, F. (1990) J. Biol. Chem. 265, 16 255–16 261]. In the present study, we elucidate the origin for this heterogeneity. Isoelectric focusing analysis of immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…4). The tissue distribution of H-FABP and I-FABP mRNA were similar to that previously reported in rat or human (3,15,16). …”
Section: Tissue Expression Pattern Of Chicken H-fabp and I-fabp Genessupporting
confidence: 79%
“…4). The tissue distribution of H-FABP and I-FABP mRNA were similar to that previously reported in rat or human (3,15,16). …”
Section: Tissue Expression Pattern Of Chicken H-fabp and I-fabp Genessupporting
confidence: 79%
“…1, lane 2). We presented arguments (31) that the isoforms stem from two different mRNAs rather than from posttranslational modification (deamidation).…”
Section: Discussionmentioning
confidence: 99%
“…Isoelectric focusing was performed under denaturing conditions as described earlier (31). Two-dimensional gel electrophoresis, which was also performed under denaturing conditions, and Western blotting were done as described by Nielsen and Spener (30).…”
Section: Methodsmentioning
confidence: 99%
“…Two isoforms of bovine H-FABP were reported, with Asp or Asn at position 98 [60]. The heterogeneity was caused by distinct mRNA species [61], but whether this is due to different genes, alternative splicing or RNA editing is not yet clear. Phelan et al [31] reported a Lys53Arg substitution in human H-FABP which had a low frequency in a Swedish population and showed no association with breast cancer incidence.…”
Section: Gene Structure and Regulation Of Expressionmentioning
confidence: 99%